Antibiotic Dispensing Practices at Community Pharmacies in Kathmandu and Lalitpur Districts of Nepal - Jha, Nisha; Shrestha, Sunil; Shankar, Pathiyil Ravi; Khadka, Anil; Ansari, Mukhtar; Sapkota, Binaya (Indian Journal of Pharmacy Practice)
Objectives: Antibiotics are often dispensed irrationally especially in community pharmacies. The present study was conducted to evaluate antibiotic dispensing practices among community pharmacies. Methods: A crosssectional study was conducted in Kathmandu and Lalitpur districts, Nepal from October to November 2018 among the community pharmacies listed in different directories. Systematic random sampling was used to sample 78 community pharmacies based on a 5% margin of error and a 95% confidence level. Data was collected using a structured questionnaire and analyzed using SPSS version 21 for Windows. Results: Out of 78 pharmacies, 54 (69.2%) were in Kathmandu district. Antibiotics were dispensed without a prescription by 67 (85.9%) pharmacies. Brand substitution was seen in 43 pharmacies (55.1%). Antibiotics per prescription were three in 51 cases (65.4), followed by two antibiotics in 27 (34.6%). Advice regarding completing the course of antibiotics was provided by 59 (75.6%) pharmacies and an insufficient course of antibiotics was dispensed in 23 (29.5%) pharmacies. Nine pharmacists (11.5%) replaced prescribed antibiotics with cheaper brands. Azithromycin [69 (22.2%)] was the most dispensed antibiotic followed closely by Amoxycillin [68 (21.9%)]. Conclusion: Dispensing antibiotics without a prescription was seen in most pharmacies which can adversely impact the rational use of antibiotics. The findings of this study may necessitate strengthening the implementation of the framed guidelines for ensuring the safe and rational use of antibiotics.
Keywords: Antibiotics; Community pharmacy; Dispensing; Kathmandu; Lalitpur; Pharmacists.